Aquatic Oligochaete Biology IX Selected Papers from the 9th Symposium on Aquatic Oligochaeta, 6-10 October 2003, Wageningen, The Netherlands - Verdonschot, Piet F.M.; Wang, Hongzhe; Pinders, Adrian; Nijboer, Rebi.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
This volume contains selected papers from the 9th Symposium on Aquatic Oligochaeta, 6–10 October 2003, Wageningen, The Netherlands. 18 contributions deal with the biology of aquatic oligochaetes, and represents a mixture of the fields of taxonomy, anatomy, morphology and physiology, life history, ecology, sludge studies and toxicology. This wide scope is in line with the recent trends in oligochaete research, with a special interest in sludge studies. Research teams from France, Japan, United States, Czech Republic, The Netherlands, Spain, Italy, Germany, Hungary and China present the latest developments on annelid studies and also reflect a balanced mixture of geographical areas, as well as biological topics.
In Memoriam: Professor Walter James Harman, PhD (1928–2002) -- In Memoriam: Professor Walter James Harman, PhD (1928–2002) -- Taxonomy, Anatomy, Morphology and Physiology -- Troglodrilus (Annelida, Oligochaeta, Tubificidae), a new genus from subterranean habitats in southwestern Europe -- Generation of bilateral symmetry in the ectoderm of the Tubifex embryo: involvement of cell-cell interactions -- Distribution pattern of ?-amino butyric acid immunoreactive neural structures in the central and peripheral nervous system of the tubificid worm, Limnodrilus hoffmeisteri -- Identification and pattern of primary sensory cells in the body wall epithelium of the tubificid worm, Limnodrilus hoffmeisteri -- Divergence of the F1-ATP synthase complex in the ice worm, Mesenchytraeus solifugus (Annelida, Clitellata, Enchytraeidae) -- Life History -- From demographic strategies to mathematical models: trends in population dynamics studies of aquatic Oligochaeta -- Asexual reproduction and segmental regeneration, but not morphallaxis, are inhibited by boric acid in Lumbriculus variegatus (Annelida: Clitellata: Lumbriculidae) -- Seasonal vertical migration and aestivation of Rhyacodrilus hiemalis (Tubificidae, Clitellata) in the sediment of Lake Biwa, Japan -- Survival and reproduction in Aeolosoma viride (Annelida, Aphanoneura) -- Ecology and Toxicology -- Ecology and biology of marine oligochaeta — an inventory rather than another review -- Habitat preferences of aquatic Oligochaeta (Annelida) in the Rokytná River, Czech Republic - a small highland stream -- Beyond masses and blooms: the indicative value of oligochaetes -- Differential response of aquatic oligochaete species to increased nutrient availability - a comparative study between Estonian and Dutch raised bogs -- Toxicity of Santander Bay sediments to the euryhaline freshwater oligochaete Limnodrilus hoffmeisteri -- Oligochaete assemblages in the hyporheic zone and coarse surface sediments: their importance for understanding of ecological functioning of watercourses -- Surface and hyporheic oligochaete assemblages in a French suburban stream -- Sludge Studies -- Sludge reduction by predatory activity of aquatic oligochaetes in wastewater treatment plants: science or fiction? A review -- Sludge reduction with a novel combined worm-reactor.
Keywords: Aquatic ecology .; Freshwater & Marine Ecology